Resolving the Climate Change Crisis : The Ecological Economics of Climate Change - Lawn, Philip (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This book explains why the climate change crisis is a symptom of a much larger underlying problem - namely, humankind's predilection with continuous GDP-growth. Given this starting point, the world's high-income nations must begin the transition to a qualitatively-improving steady-state economy and low-income nations must follow suit at some stage over the next 20-40 years. Unless they do, a well-designed emissions protocol will be as useless as the paper it is written on. Adopting an ecological economic approach, this book sets out why we must abandon the goal of continuous growth; how we can do so in a way that improves human well-being; what constitutes a safe atmospheric concentration of greenhouse gases; and what type of emissions protocol and emissions-trading framework is likely to achieve a desirable climate change outcome. Failure of the world's leaders to achieve these goals will not only put future human well-being at risk, it will threaten freedom in the liberal-democratic tradition and international peace.
Part I. Ecological Economics, Climate Change, and Sustainable Development -- Chapter 1.Ecological Economics and Climate Change -- Chapter 2. Sustainable Development and Climate Change -- Chapter 3. Policies to Achieve Sustainable Development -- Chapter 4. A Sustainable Versus a Growth-As-Usual Scenario -- Part II. Alternative Perspectives of the Climate Change Crisis -- Chapter 5. A Mainstream Economic Perspective of the Climate Change Crisis -- Chapter 6. An Ecological Economic Perspective of the Climate Change Crisis -- Part III. A Way Forward and the Road to Sustainable Development -- Chapter 7. The Case for an Emissions-Trading System to Help Resolve the Climate Change Crisis -- Chapter 8. International Climate Change Institutions and the Greenhouse-Gas Emitting Performance of Nations -- Chapter 9 Laying the Foundations to Support a New Global Climate Change Protocol -- Chapter 10. A Post-2020 Protocol and Emissions-Trading Framework to Resolve the Climate Change Crisis.
Description based on publisher-supplied MARC data.
Keywords: Climate change; Development economics; Economic policy; Environmental economics; Sustainable development; Environmental Economics; Climate Change; Development Economics; Economic Policy; Sustainable Development